Non-performing loans and systemic risk: comparative analysis of Serbia and countries in transition CESEE - Vukovic, Vlastimir; Domazet, Ivana S (Industrija, 2013)
This paper presents the results of the research on the impact of non-performing loans to the systemic risk in the domestic banking system and a comparison with other countries in transition, as well as on certain EU countries. It is important to metion that the extreme bank-centricity caused the extension of the analysis to the entire financial sector of Serbia. Therefore, macroeconomic and macro-financial component of systemic risk were separated. In order to more precisely determine the main effects of non-performing loans in the propagation of systemic risk, the authors have created and used two new synthetic indicators in the research. The first is the macroeconomic contagion with non-performing loans (problematic loans expressed as a percentage of GDP), and the second is the infection of financial sector with non-performing loans (the proportional share of these loans in the assets of the financial sector). Analysis of the period just before and during the current financial crisis and the recession (2007-2012) showed that the NPLs (non-performing loans) are the main generator of systemic risk in the financial and real sectors of Serbia. In addition, the survey results show that the applied synthetic indicators measure total system risk and its basic components more accurately then the analytical, which have only been in use until now. Comparative analysis showed similar results, not only in the countries in transition, but also in developed ones. The results of this study provide guidance and represent an important input for economic policymakers, because the systemic risk is the greatest immediate threat to economic prosperity and financial stability of each country
Keywords: non-peforming loans; systemic risk; macroeconomic contagion; banks; financial sector